History of Depression and Frontostriatal Connectivity during Reward Processing in Late Adolescent Boys - Morgan, Judith K. (J Clin Child Adolesc Psychol, 2015)
OBJECTIVE: Given that depression in men is associated with risk for seriously adverse consequences, evaluating how putative neural mechanisms of depression—such as reward-related frontostriatal connectivity—may be altered in late adolescent boys with a history of depression is an important research aim. Adolescents and adults with depression have been demonstrated to show blunted striatal response and heightened medial prefrontal cortex (mPFC) activation to winning reward. Function in reward circuits appears to be best understood as coordination of regions within frontostriatal circuitry, and alterations to this circuitry could occur in those with a history of depression. METHOD: The current study evaluated functional connectivity between the nucleus accumbens and mPFC in a sample of 166 ethnically-diverse boys with and without a history of depression. Participants completed an fMRI monetary reward paradigm at age 20. Lifetime history of depression and other psychiatric illnesses was measured prospectively and longitudinally, using structured clinical interviews at 7 time points from ages 8 to 20. RESULTS: Boys with a history of depression showed heightened positive connectivity between the nucleus accumbens and the mPFC relative to boys with no psychiatric history when winning rewards relative to losing rewards. This altered frontostriatal connectivity pattern was also associated with greater number of depressive episodes in the boys’ lifetime. CONCLUSIONS: History of depression in late adolescent boys may be associated with altered coordination between the nucleus accumbens and mPFC when winning reward. This coordination could reflect over-signaling of the mPFC to dampen typical VS response or enhance weak VS response.